(untitled) (Proceeding of Saizu International Conference on Transdisciplinary Religious Studies, 2021)
This study aims to describe the teachers’ problems in implementing online learning during pandemic era at State Madrasa Ibtidaiyah 3 Central Aceh. The research method uses descriptive qualitative. Data collection techniques through observation, interviews and documentation. The results of the study show that the teachers’ problematic in implementing online learning during the Covid-19 pandemic related to the limitations of teacher competence in using technology, some students do not have an android for online learning, very little time to manage online learning, difficulties in making online learning media, limited internet network availability and expensive internet quotas, lack of parental supervision in carrying out learning. To overcome this problem, various efforts have been made, such as: attending training or seminars related to online learning, giving assignments to students via Short Message Service or students taking assignments to school, participating in training to create online learning media, increasing online learning time, teachers providing funds for internet quotas, the teacher coordinates with the parents. Although many problems are felt by teachers during pandemic, they continue to try to implement online learning to students so that the expected learning objectives are achieved even though they are not optimal.